Characterization of political leadership: usability and dynamics of interaction in Twitter: Multiple case studies in Ecuador - Luzuriaga Uribe , Estefanía; Baquerizo-Neira, Gabriela (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This research approaches the use of social networks in electoral campaigns. It identified how candidates for local authorities in Ecuador build their image on Twitter. The methodology was content analysis to identify the usability of the different available resources (hashtags, photographs and videos), the main themes that emerge from the candidates official accounts on this digital platform and direct mentions for the conformation of the network. The results show how these political leaders use the features of Twitter to project an image and the networks of communications that are generated by these sectional leaders during the political campaign.